Safety and efficacy of rivaroxaban for the secondary prevention following acute coronary syndromes among biomarker-positive patients: Insights from the ATLAS ACS 2-TIMI 51 trial. Issue 2 (1st March 2019) - Korjian, Serge; Braunwald, Eugene; Daaboul, Yazan; Verheugt, Freek; Bode, Christoph; Tendera, Michal; Jain, Purva; Plotnikov, Alexei; Burton, Paul; Gibson, C Michael
Abstract: Background: Despite dual antiplatelet therapy, persistent thrombin generation and thrombin-mediated platelet activation account in part for the residual risk of atherothrombotic disease among patients with prior acute coronary syndrome (ACS). Inhibition of thrombin generation among high-risk ACS patients (biomarker-positive ACS) with the factor Xa inhibitor rivaroxaban may limit ongoing thrombus formation and myocardial necrosis and thereby improve clinical outcomes. Objectives and methods: ATLAS ACS 2-TIMI 51 was a double-blind, placebo-controlled clinical trial that randomized ACS patients to either rivaroxaban 2.5 mg b.i.d., rivaroxaban 5 mg b.i.d., or placebo plus standard-of-care antiplatelet therapy for a mean of 13.1 months and up to 31 months ( N =15, 526). This post-hoc analysis evaluates the safety and efficacy of rivaroxaban among biomarker-positive ACS patients with and without a history of prior stroke of transient ischemic attack in the ATLAS ACS 2-TIMI 51 trial. Results: A total of 12, 626 biomarker-positive ACS patients were included in this analysis. Among biomarker-positive patients without a prior history of stroke or transient ischemic attack, rivaroxaban 2.5 b.i.d. was associated with a reduction in the primary efficacy endpoint (composite of cardiovascular death, myocardial infarction, or stroke) as compared with placebo (hazard ratio=0.80, 95% confidence interval (0.68–0.94), p =0.007) at the expense of an increase in non-coronary-artery-bypass-graft-related Thrombolysis in Myocardial Infarction major bleeding (1.9% vs . 0.7%, p <0.0001), but not a significant increase in either intracranial hemorrhage (0.4% vs . 0.2%, p =0.11) or fatal bleeding (0.1% vs . 0.3%, p =0.16). Conclusion: Rivaroxaban 2.5 mg b.i.d. was associated with a significant reduction in the composite of cardiovascular death, myocardial infarction, or stroke with no increase in fatal bleeding. Biomarker-positive patients with no prior history of stroke or transient ischemic attack may be a optimal target population to receive "dual pathway" therapy with rivaroxaban plus dual antiplatelet therapy for secondary prevention following ACS.